2018
DOI: 10.1186/s12879-018-3322-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of crowd-sourced, electronic health records based, and traditional health-care based influenza-tracking systems at multiple spatial resolutions in the United States of America

Abstract: BackgroundInfluenza causes an estimated 3000 to 50,000 deaths per year in the United States of America (US). Timely and representative data can help local, state, and national public health officials monitor and respond to outbreaks of seasonal influenza. Data from cloud-based electronic health records (EHR) and crowd-sourced influenza surveillance systems have the potential to provide complementary, near real-time estimates of influenza activity. The objectives of this paper are to compare two novel influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…The children with age of >14 were examined in the 2016/2017 epidemic season, and the results demonstrated that children due to immature immunity are at particular risk for influenza (Cieslak et al, 2018). In the United States, Baltrusaitis et al found that data from novel influenza surveillance systems can complement with traditional healthcare-based systems at multiple spatial resolutions (Baltrusaitis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The children with age of >14 were examined in the 2016/2017 epidemic season, and the results demonstrated that children due to immature immunity are at particular risk for influenza (Cieslak et al, 2018). In the United States, Baltrusaitis et al found that data from novel influenza surveillance systems can complement with traditional healthcare-based systems at multiple spatial resolutions (Baltrusaitis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…10 Studies in the Unites States and Portugal also found good agreement between sentinel GP surveillance data and alternative databases using EMR, with correlations ranging between 0.78 and 0.99. 11,12 In ASPREN, a rise in ILI cases started earlier each year compared with MedicineInsight which is probably related to the increase in other acute respiratory infections, particularly URTI, as identified in MedicineInsight. Because GPs can label the same set of respiratory symptoms differently, 9 it is plausible that ASPREN GPs might code other respiratory infections as ILI because of their role in the sentinel system (ie observer bias).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the limitations of epidemiological surveillance, internet-based technologies have been developed to estimate and monitor real-time changes in population, soliciting participation from the public at large [ 12 , 13 ]. One approach that has been introduced is self-reported symptom tracking.…”
Section: Introductionmentioning
confidence: 99%